Exploring the Potential of Low-Temperature Vacuum Drying for Red Cabbage: Focus on Bioactive Compound Retention and Associated Antioxidant, Cytotoxic, and Antimicrobial Properties - Romero-Figueroa, J (John Wiley and Sons Inc, 2026)
Low-temperature vacuum drying (LTVD) presents considerable potential for processing cruciferous vegetables due to its ability to preserve thermosensitive compounds. However, the process effects at different LTVD temperatures remain underexplored. In this study, red cabbage was dried at 15°C, 25°C, 35°C, and 45°C under a constant vacuum of 10 mbar. Drying kinetics, the retention of bioactive compounds, and associated antioxidant, cytotoxic, and antimicrobial activities were evaluated. The Midilli–Kucuk model and its modified version accurately described the drying behavior. Liquid chromatography–high-resolution mass spectrometry (LC–HRMS) analysis identified glucobrassicin (GBC) as the predominant glucosinolate, optimally retained at 25°C, whereas chlorogenic acid (CGA) and sinapoyl d-glucoside (SDG) were better preserved at 15°C. The anthocyanin content retention at 45°C was comparable to that achieved by freeze-drying (FD). Multivariate analysis revealed that sinapoyl derivatives were the major contributors to antioxidant and cytotoxic activities. Supercritical CO2 extracts exhibited notable antimicrobial activity (inhibition halos ≥10 mm), particularly in samples dried at 15°C and 25°C. These findings suggest that LTVD could serve as a viable alternative to FD, as LTVD retained bioactive compounds and bioactivity to a comparable extent in relation to FD, particularly at 15°C and 25°C. Practical Applications: This study shows that LTVD can effectively preserve health-promoting compounds in red cabbage, offering a promising alternative to FD. LTVD at 15°C and 25°C could be applied in the food industry to develop functional ingredients or powders with retained antioxidant, antiproliferative, and antimicrobial properties, using a less energy-intensive process. © 2026 Institute of Food Technologists.